New Essays on Musical Understanding - Kivy, Peter 1934-2017 (Oxford Clarendon, 2001)
Peter Kivy presents a selection of his new and recent writings on the philosophy of music--an area to which he has been one of the most eminent contributors. In his distinctively elegant and informal style, Kivy explores such topics as musicology and its history, the nature of musical works, and the role of emotion in music, and does so in a way that will attract the interest of philosophical and musical readers alike. Most works are published here for the first time, each one unique and accessible, making this collection a delight both to followers of Kivy's work and to first-time readers.
Keywords: Music philosophy and esthetics